Inhibition of cellular methyltransferases promotes endothelial cell activation by suppressing glutathione peroxidase 1 protein expression - Barroso, Madalena (2014)
Background: Methylation of tRNASec facilitates the incorporation of selenocysteine at a UGA codon during translation. Results: Accumulation of the homocysteine precursor S-adenosylhomocysteine decreases tRNASec methylation, reducing glutathione peroxidase 1 expression and increasing oxidative stress-induced inflammatory activation of endothelial cells. Conclusion: Methylation modulates the expression of selenoproteins to regulate redox-dependent inflammatory pathways. Significance: Hypomethylation stress promotes a proatherogenic endothelial cell phenotype.